LINGUISTICS AND ARTIFICIAL INTELLIGENCE: NEW APPROACHES TO LANGUAGE (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This article explores the convergence of linguistics and artificial intelligence (AI), focusing on new methods in language processing, understanding, and generation. AI has rapidly advanced linguistic applications in natural language processing, speech recognition, and machine translation, reshaping communication and knowledge representation. By analyzing linguistic structures, AI systems improve in accuracy and contextual understanding, contributing to advancements in automated language tasks. We discuss current approaches, challenges, and implications for future research in the AI-linguistics interface.